Analisis Kesulitan Belajar Subtest Penalaran Matematika bagi Siswa yang Mengikuti UTBK - Karina Aulia Putri; Nadya Amelia Putri Firman; Aliyatun Nur Afifah; Ahmad Fu'adin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze learning difficulties in the mathematical reasoning subtest for students taking the Computer-Based Writing Examination (UTBK). The mathematical reasoning subtest is an important part of measuring students' abilities in solving high-level mathematical problems. The research method used was quantitative analysis of UTBK results data as well as in-depth interviews with a number of students.The results of the analysis show that the majority of students have difficulty understanding the mathematical concepts underlying the reasoning subtest. Factors such as a lack of understanding of basic concepts, less effective learning methods, and exam anxiety may be the main causes of these difficulties. Apart from that, these findings also indicate that there is a gap in students' preparation for the types of mathematical reasoning questions tested in UTBK. Developing more interactive and in-depth learning strategies, providing intensive academic guidance, and improving metacognitive skills can be a solution to overcome these learning difficulties. In addition, this research suggests that UTBK administrators and educational institutions pay special attention to understanding basic mathematical concepts at the upper secondary education level in order to increase students' readiness for exams. By understanding the difficulty of learning the mathematical reasoning subtest, it is hoped that it can make a positive contribution in formulating more effective educational policies, as well as providing direction for teachers and educational institutions in improving the quality of mathematics learning at the high school level.